2015
DOI: 10.1111/1750-3841.13141
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Malpighia Punicifolia and Extension of Water Buffalo Steak Shelf‐Life

Abstract: In the present study, a multiple approach was used to characterize Malpighia punicifolia extract and to evaluate its inhibitory activity against several meat spoilage bacteria. First, volatile fraction, vitamins and phenolic compounds of the extract obtained by supercritical fluid extraction were determined by GC‐MS and HPLC. Then, the antimicrobial action of the extract was in vitro evaluated against Pseudomonas putida DSMZ 291T, Pseudomonas fluorescens DSMZ 50009T, Pseudomonas fragi DSMZ 3456T, and Brochothr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…The antimicrobial activity of the strains was conducted according to the agar well diffusion assay described by Tremonte et al [29] with same modifications. Briefly, 20 mL of BHI soft agar (0.7% agar) inoculated with an overnight culture of each indicator strain (final concentration of about 7 Log CFU/mL) were poured in Petri plates.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial activity of the strains was conducted according to the agar well diffusion assay described by Tremonte et al [29] with same modifications. Briefly, 20 mL of BHI soft agar (0.7% agar) inoculated with an overnight culture of each indicator strain (final concentration of about 7 Log CFU/mL) were poured in Petri plates.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Studies on the microbial cell surface have shown that the presence of (glycol-) proteinaceous material results in higher hydrophobicity, whereas hydrophilic surfaces are associated with the presence of polysaccharides [24,29]. Hydrophobic cell surfaces were demonstrated to be highly adherent-more than 40%-to apolar solvents [24,43].…”
Section: Hydrophobicitymentioning
confidence: 99%
“…In the last years, several bio-control strategies have been developed to improve the safety and to extend the shelf-life of various foods. In this field, protective microbial cultures ( Sorrentino et al, 2013 ; Tremonte et al, 2017a ) and treatments with natural substances ( Reale et al, 2011 ; Tipaldi et al, 2011 ; Catalano et al, 2015 ; Tremonte et al, 2016a ) showed positive effects. The use of natural compounds, in particular antimicrobials produced by protective cultures, may represent an important tool in the food biopreservation, also considering the consumer demand for safe and healthy foods, in terms of reduction in chemical additives and provision of beneficial effects ( Reale et al, 2011 ; Succi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to L. innocua , pathogenic L. monocytogenes is frequently found in various foodstuffs (Kovacevic et al, 2012; Jami et al, 2014; Ebner et al, 2015; Melo et al, 2015), especially those characterized by pH values higher than 4.4 (CAC, 2009). In the food industry a number of strategies are used to inhibit the growth of undesirable microorganisms, like technological processing (Tremonte et al, 2014), addition of natural substances (Tipaldi et al, 2011; Tremonte et al, 2016), protective microbial cultures (Sorrentino et al, 2013) as well as organic acids (Davidson et al, 2013). Unfortunately, in the case of several food types, sub-lethal pH values may induce resistance mechanisms to acid stress, which make the cells more resistant to severe acid conditions (Gandhi and Chikindas, 2007).…”
Section: Introductionmentioning
confidence: 99%